2013
DOI: 10.1159/000351098
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Infections in a Tertiary Care Hospital in Mexico over the Past 13 Years

Abstract: Background:Acinetobacter baumannii has evolved from an opportunistic pathogen into a common and persistent nosocomial bacterium capable of causing severe infections during endemic and epidemic periods. Methods: The study period extended from January 1999 to December 2011 and involved patients hospitalized at the Hospital Civil de Guadalajara, Fray Antonio Alcalde, Jalisco, Mexico. From each patient, a single isolate was obtained, and a total of 3,680 unique isolates were collected. Susceptibility tests were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
(32 reference statements)
4
28
0
2
Order By: Relevance
“…However, carbapenem-resistant isolates have been increasing worldwide [2,12,13,14,15]. In recent years, carbapenem resistance rates were reported to be over 50% [16,17,18,19,20,21], and in our last study it was found to be 92% in intensive care units [18]. Carbapenem-resistant A. baumannii poses a significant threat in hospitals, as therapeutic options are limited.…”
Section: Discussionmentioning
confidence: 88%
“…However, carbapenem-resistant isolates have been increasing worldwide [2,12,13,14,15]. In recent years, carbapenem resistance rates were reported to be over 50% [16,17,18,19,20,21], and in our last study it was found to be 92% in intensive care units [18]. Carbapenem-resistant A. baumannii poses a significant threat in hospitals, as therapeutic options are limited.…”
Section: Discussionmentioning
confidence: 88%
“…This study showed that the A. baumanii isolates were mostly multi-drug resistant, and 55.6% of these were carbapenem-resistant. Recent studies from various countries also showed that rates of carbapenem-resistant A. baumanii (CRAB) varied from 55% to 88% and increased particularly in association with neurosurgical infection [5,17,18]. The high incidence of CRAB is a great concern in terms of nosocomial infection and it had been associated with serious therapeutic problem [5,17].…”
Section: Discussionmentioning
confidence: 99%
“…Se analizaron 3.680 aislamientos y se encontró que la diseminación se inició en una unidad de cuidados intensivos de pacientes adultos. Se observó que la sensibilidad a meropenem disminuyó entre 1999 y 2012 (de 92 a 12 %), y que diferentes clones de A. baumannii producían VIM-4, IMP-1 y OXA-24; el microorganismo se aisló más frecuentemente en secreciones y afectó a pacientes que por la gravedad de su cuadro de ingreso (neurocirugía, medicina interna) fueron estabilizados primero en la unidad de cuidados intensivos para después ser trasladados a los servicios hospitalarios del caso (50,51).…”
Section: Acinetobacter Baumanniiunclassified
“…Gracias a las contribuciones mencionadas, en nuestro país hemos identificado las tendencias de resistencia, así como la epidemiologia hospitalaria, el tipo de bacterias implicadas y su evolución (51,72).…”
Section: Conclusionesunclassified